Prevailing Factors of Subjugation in Chan's The School for Good Mothers - Huda Irshad Siddiqui; Wajiha Bakhtiyar (University of Chitral Journal of Linguistics and Literature)
The current study aims to investigate the oppression and injustice in a dystopian society that subjugates the feminine figure in Chan's The School for Good Mothers. The objectives of the study are constructed as overlapping variables to oppress the protagonist of the story and a realistic portrayal of a despotic society where motherhood is violated. The research gap has been defined as the socially produced conventional image of a mother who is suppressed by society. The study attempts to underline the idea of an imperfectly perfect society that seeks perfection in mothers through the lens of an intersectional feminist theory of Kimberle Crenshaw, Demarginalising the Intersection of Race and Sex (1989), and Mapping the Margins (1991). The study is qualitative and interpretive to the text that identifies the prevailing elements of oppression as well as the emotional breakdown a mother experience. The cruelty of the system and inaccurate assessment of parental practices are the outcomes of the data analysis. The study will bring about a radical shift in society where women will be respected and valued, and the success or failure of a mother's commitment will no longer be determined by her actions.